Development of Management Information System Rental Service Photography Web-Based Using PHP Native Case Study at PT Dwipa Photowork Surabaya - Ahmad Habib; Rifki Satya; Balok Hariadi (Jurnal Mantik, 2022)
Scheduling is a planning activity to determine when and where each surgery as part of the work in total must be carried out on limited energy sources, and the allocation of energy resources at a certain time by taking into account the available resource capacity. In this research, utilizing the development of information technology, the most important is the application system for data processing or data collection that functions to produce the required information. Every company that wants to develop its business and achieve success, of course, the company must follow the information age by using computer applications that make it easy to process company data.  In this study, the author wants to provide a solution by designing an application for processing work service scheduling flow data based on the manual scheduling system that already exists at the Dwipa Photowork Company which is still less effective and efficient, and creates a database system used in a well-computerized scheduling application. between the database system, the user interface, and the user itself